How authoritarian is the environmental governance of China?. Issue 54 (December 2015) - Lo, Kevin
Highlights: China's low-carbon governance appears highly authoritarian. Local experience is more ambiguous, displaying a mixture of authoritarian and liberal features. This is because the central government has failed to control local actors. Abstract: This paper challenges the prevailing perception that the environmental governance of China is a case exemplar of authoritarian environmentalism. Using low-carbon governance as an example, it shows that although China's national low-carbon policy appears highly authoritarian, the situation on the ground is much more ambiguous, displaying a mixture of authoritarian and liberal features. While China's top-down and non-participatory policy environment has been crucial in stimulating a low-carbon transition, the failure of the central government to control local actors has created a situation of de facto neoliberal environmentalism, where local governments and energy-intensive enterprises enjoy a high degree of freedom and flexibility to manage their own energy consumption in spite of the overt authoritarian rule. The findings of this research show that viewing China's environmental governance as a clear-cut instance of authoritarian environmentalism should be done with circumspection, and that studying the nature of environmental governance as a complex process requires a thorough understanding of not just national policy but also local politics and the ways the two are connected.